An Analysis of Cybersecurity Subject and Vilanets Learning Media Towards Vocational School Students’ Digital Skills - Santyadiputra, Gede Saindra; Kustono, Djoko (Letters in Information Technology Education (LITE), 2023)
Digital skills are crucial to accessing jobs, business opportunities, and information. The vocational school is vital in fulfilling Human Resources (HR) and future workforce candidates. Therefore, subject and learning media are needed to accommodate students' digital skills. The analysis methods are Strength, Weakness, Opportunity, and Threat (SWOT) and Systematic Literature Review (SLR). Cybersecurity is a desirable talent area of the future and is one of the digital skills competency areas. The results map the alignment of the scope of the Cybersecurity subject material and Vilanets learning media. These results can be used as a reference for the digital skills of students in vocational schools.